The Behavioral Neuroscience of Drug Discrimination (Current Topics in Behavioral Neurosciences,, 2018)
The goal for this volume is to provide an up-to-date review of the discriminative stimulus properties of major psychoactive drug classes with an emphasis on how this paradigm enhances our understanding of these drugs and how these findings translate from animals to humans. The drug discrimination paradigm applies to both drugs of abuse and drugs for treating mental illnesses, and research from these studies has provided immense translational value for learning about the mechanisms responsible for drug effects in humans.